DESKRIPTIF IMPLEMENTASI PEMBELAJARAN FISIKA TERINTEGRASI STEM DI INDONESIA DAN FILIPINA - Putri, Ananda Resya; Dwandaru, Wipsar Sunu Brams; Viyanti, Viyanti; Anggreini, Anggreini; Cayabyab, Hazel Ann M. (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This study aims to describe and compare the implementation of integrated STEM physics learning in Indonesia and the Philippines. The study uses a qualitative descriptive research design, with non-test instruments in the form of questionnaires, interviews, and document analysis. The research subjects consisted of 11th grade students at SMAN 16 Bandar Lampung and 12th grade students in the STEM program at BUCEILS-SHS Philippines. Data validity was tested through source triangulation, while data analysis was conducted using Creswell's qualitative analysis stages. The questionnaire results showed that the implementation of integrated STEM physics learning in the Philippines obtained a percentage of 82% in the excellent category, while in Indonesia it was 75% in the good category. These findings were supported by the results of teacher interviews and learning tool analysis, which showed the integration of science, technology, engineering, and mathematics aspects through contextual learning and problem solving activities. The novelty of this study lies in its empirical comparative evidence that demonstrates how differences in national curriculum structures directly influence the depth, consistency, and effectiveness of integrated STEM physics learning implementation across countries. While previous studies have examined integrated STEM physics learning within single national contexts, field-based cross-country comparative evidence remains limited. This study addresses this gap by providing empirical data comparing STEM implementation indicators in Indonesia and the Philippines. The implications of the study indicate the need for curriculum policy support and strengthening of teacher competencies to optimize the implementation of STEM in physics learning.